3D modeling strategies for simulating electromagnetic superposed forming processes. (April 2018) - Long, Anlin; Wan, Min; Wang, Wenping; Wu, Xiangdong; Cui, Xuexi
Highlights: The optimized modeling strategy for predicting deformation is valid and feasible. Relative deviation between experimental and simulation results is less than 5%. Approximately 90% of computational time-cost could be saved by shell elements. Numerical hourglass in bending simulations could be solved by shell elements. Abstract: Electromagnetic superposed forming (EMSF) is a novel forming method which is aimed at forming large scale sheet specimens using pulsed electromagnetic (EM) force and multi-point punch matrix. A large number of computational resources are then needed for corresponding numerical simulations. This paper introduces the modeling strategies for predicting the specimen deformation in EMSF. The large size specimen is substituted by a small specimen that is wide enough to cover the electromagnetic field during solving the EM forces. The forces are then translated and applied to specific locations of the large specimen where the coil works. For deformation analysis, the shell elements are used to model the dynamic behavior of the specimens, which has not been studied in the former simulations of electromagnetic forming (EMF). The results show that the strategies are valid and dramatic time-saving in simulating the forming procedures. The relative deviation between simulations and experiments is less than 5% and the decrement of computational time-cost is approximately equal to 90%. The numerical hourglass which is an outstanding problem in bending simulation could be inhibited by using shell elements. Graphical abstract: Image, graphical abstract